Factors Influencing the Utilization of Antenatal Care Services Among Women of Reproductive Age (15 – 49 Years) in Garowe, Puntland State of Somalia. - Ali, Abdullahi Ahmed (Amref International University, 2025)
Background: Approximately one thousand women die daily worldwide from pregnancy complications. In Somalia, only 6% of women aged 15-49 receive the recommended four antenatal care (ANC) visits, with 29% attending their first visit before the fourth month of pregnancy. Limited studies have focused on the burden of antenatal care uptake in Garowe, Puntland, Somalia. Broad Objective: This study aimed to determine the factors influencing ANC utilization among reproductive-aged women in Garowe, Puntland, Somalia. The objectives include establishing demographic, economic, health facility, and cultural factors affecting ANC utilization. Methods: A mixed methods approach was used, involving cluster sampling of 384 women with children under 12 months and purposive sampling of eight healthcare providers and four administrative leaders. Data was collected through structured questionnaires and key informant interviews. Data was analysed using descriptive and inferential statistics with SPSS version 28. Demographic and clinical characteristics were analysed descriptively, while ANC uptake was calculated as a proportion. Logistic analysis was used to obtain factors influencing ANC utilization. Thematic analysis was used for qualitative data. Findings: The response rate was 100%. The average age of respondents was 30.2 years, with 50.8% aged less than 35 years. Most respondents (84.6%) were married, 35.7% had no formal education, and 61.2% were housewives. Low ANC uptake was observed in 56.8% of respondents. Factors associated with low ANC utilization included lack of insurance, use of public transport, and cultural norms discouraging ANC attendance. Conclusion and Recommendations: ANC utilization was low, with 56.8% having less than four ANC visits. It is recommended to work with community leaders, healthcare workers, and local organizations to raise awareness about the importance of ANC and conduct educational sessions to inform women and their families about the benefits of regular prenatal care.
Keywords: Antenatal Care; Reproductive Women; Somalia